2007
DOI: 10.1002/hed.20662
|View full text |Cite
|
Sign up to set email alerts
|

Results of a pilot study of the effects of celecoxib on cancer cachexia in patients with cancer of the head, neck, and gastrointestinal tract

Abstract: Background. Animal models suggest that cyclooxygenase-2 (COX-2) inhibitors may be beneficial in suppressing cancer cachexia. We investigated the effect of short-course celecoxib on body composition, inflammation, and quality of life (QOL) in patients with cancer cachexia in a phase II clinical pilot trial.Methods. Eleven cachectic patients with head and neck or gastrointestinal cancer were randomly assigned to receive placebo or celecoxib for 21 days while awaiting the initiation of cancer therapy. Body compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
96
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(100 citation statements)
references
References 25 publications
2
96
0
2
Order By: Relevance
“…In selecting the agents, we had originally planned to include the most selective cyclo-oxygenase 2 inhibitor, celecoxib, on the basis of the results observed in our phase II study [16] and in other authors' studies [61][62][63]; however, we eventually decided to not include this drug because of cardiotoxicity safety concerns that emerged in 2005 and that led to the withdrawal of rofecoxib from the market and restriction on the use of celecoxib.…”
Section: Discussionmentioning
confidence: 99%
“…In selecting the agents, we had originally planned to include the most selective cyclo-oxygenase 2 inhibitor, celecoxib, on the basis of the results observed in our phase II study [16] and in other authors' studies [61][62][63]; however, we eventually decided to not include this drug because of cardiotoxicity safety concerns that emerged in 2005 and that led to the withdrawal of rofecoxib from the market and restriction on the use of celecoxib.…”
Section: Discussionmentioning
confidence: 99%
“…Out of these inhibitors only two (celecoxib and meloxicam) have been widely used to study Cox2 mediated muscle loss [73,74,77]. [78]. This reflects its effectiveness in treating cancer cachexia.…”
Section: Cox2 Inhibitorsmentioning
confidence: 98%
“…There are four studies investigating the relationship between non-steroidal anti-inflammatory drugs (NSAIDs) and cancer cachexia [158][159][160][161] . These studies demonstrated improved quality of life, performance status, inflammatory markers, weight gain and survival.…”
Section: Non-steroidal Anti-inflammatory Drugsmentioning
confidence: 99%